PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGRI 001 KECAMATAN SINABOI - Kamarianto Kamarianto; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is based on the low of IPS study result of fourth grade students of SDN 001 Sinabaoi of academic year 2015/2016. Preliminary data received by the researchers, from 28 students who achieved the value of KKM only 7 students (25%). This research is a classroom action research conducted collaboratively and participatively in collaboration with fourth grade IPS teacher SDN 001 Sinaboi. The instrument of this study consists of learning devices used in this study based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The result of research got the activity of teacher at first cycle of meeting I that is 60% with enough category, second meeting of cycle I that is 75% with good category. At siklu II meeting 1 is 80% with good category and second meeting second cycle is 95% with very good category. Then the student activity is also getting better. The result of the first activity percentage of first cycle cycles is 55% with enough category, in the second meeting of the first cycle is 75% with good category. In the second cycle of meeting I is 85% with good category, and meeting II is 90% with very good category. As for the result of student learning that complete before held action only 7 student (25%) with average value 64,5. In the daily test I cycle I the number of completed students increased to 13 students or (46.43%) with an average value of 75.2. Furthermore, in the second cycle II repetition increased again with a total number of students who complete 25 students or (89.28%) with an average score of 83.93. The increase that occurred on student learning outcomes between the basic score of one cycle with an average of 16.58 and between the basic score of the second cycle with an average of 30.12 This means that the classical value obtained by students has been above the predefined KKM.Keywords: Problem-based leraning model, Learning outcomes IPS